The Role of Presenting Exclusive Breastfeeding for The Prevention of Stunting Based on The Culture of Tudang Sipulung - Elis, Andi; Mustari, Rohani; Marlina, Marlina (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The prevalence of stunting in Indonesia is increasing. The efforts to prevent stunting can be done by giving exclusive breastfeeding. This study aims to identify and assess changes in knowledge, attitudes and actions of mothers in exclusive breastfeeding for prevention of stunting before and after health education interventions based on Tudang Sipulung in the treatment group and the control group at Puskesmas Jumpandang Baru and Puskesmas Pattingaloang Makassar in 2020. The type of this research is "Quasy Experiment", pre-test and post-test with control group design. The sample in this study was divided into two groups. The instruments are questionnaires and leaflets. The data were analyzed using the Mann Whitney U test. the test result (p = 0.011) on knowledge. The result of the postpartum mother’s attitude (p = 0.000) and the post-partum mother’s actions showed the result (p = 0.000). There is an effect of-based health education interventions Tudang Sipulung.